The Relationship Between Perceptual Motor Skills and Attention. - de Sousa, Vanessa; Rueda, Fabián J. M. (Paideia (0103863X))
Although the relationship between perceptual motor skills and attention is reported in the literature, few studies have empirically explored this association. Thus, the objective of this study was to investigate the relationship between these constructs, using the Bender-Gestalt Test: Gradual Scoring System (B-SPG) and the Psychological Battery for Attention Assessment (BPA). The participants were 320 children from four public schools in a city located in the South of the state of Minas Gerais, with ages ranging from seven to 10 years (M = 8.39, SD = 1.10) and 196 (55.9 %) female. The results showed negative, moderate and significant correlations between the total scores of the instruments, indicating the relationship between the constructs. Although the data has confirmed the existence of a relationship between perceptual motor skills and attention, further studies with samples from other regions are necessary.